Journal, Memorials and Letters of Cornelis Matelieff de Jonge : Security, Diplomacy and Commerce in 17th-century Southeast Asia - Matelief, Cornelis, de jonge, 1570-1632 (NUS Press, 2015)
Admiral Cornelis Matelieff de Jonge, a Director in the Rotterdam chamber of the Dutch East Indies Company (VOC) for three decades during the early 17th century, set sail from the Dutch Republic for Asia in 1605. He launched an attack on Portuguese Melaka in 1606 and subsequently signed landmark treaties with the rulers of Johor (1606) and Ternate (1607). After returning to the Netherlands in the autumn of 1608, he wrote a series of epistolary reports and memoranda that were carefully studied by leading policy makers in the Republic, among them the renowned jurist Hugo Grotius, and the statesman Johan van Oldenbarnevelt. These materials yield candid insights into key issues of trade, security, the diplomacy of regional polities and relations with Spain and Portugal, and they contributed substantially to the formulation of early VOC policy for the Southeast Asian region in the period 1605-20. Here translated into English for the first time, and illustrated with 70 drawings and maps from the period, this collection of treaties, reports and excerpts from Matelieff's travelogue make a substantial contribution to Southeast Asian and early colonial history, international relations and international law.--